2012
DOI: 10.1242/jeb.064048
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in response to dietary salt stress: Na+ and K+ transport by the gut ofDrosophila melanogasterlarvae

Abstract: SUMMARYDrosophila provides a useful model system for studies of the mechanisms involved in regulation of internal ion levels in response to variations in dietary salt load. This study assessed whether alterations in Na + and K + transport by the gut of larval D. melanogaster reared on salt-rich diets contribute to haemolymph ionoregulation. Na + and K + fluxes across the isolated guts of third instar larvae reared on control or salt-rich diets were measured using the scanning ion-selective electrode technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
27
2
Order By: Relevance
“…For example, ion transport mechanisms of the gut epithelia of larval Drosophila are reconfigured during dietary salt stress so that there are reductions in K + and Na + absorption and increased K + and Na + secretion (Naikkhwah and O'Donnell, 2012). In the present study, we showed that NKA and VA activity in the FAMG of C. riparius larvae acclimated to varying salinity remain largely unaltered (Fig.2B, Fig.3B).…”
Section: Differences In Nka and Va Activity In Different Rearing Envisupporting
confidence: 53%
“…For example, ion transport mechanisms of the gut epithelia of larval Drosophila are reconfigured during dietary salt stress so that there are reductions in K + and Na + absorption and increased K + and Na + secretion (Naikkhwah and O'Donnell, 2012). In the present study, we showed that NKA and VA activity in the FAMG of C. riparius larvae acclimated to varying salinity remain largely unaltered (Fig.2B, Fig.3B).…”
Section: Differences In Nka and Va Activity In Different Rearing Envisupporting
confidence: 53%
“…SIET makes use of an ion-selective microelectrode that is moved between two positions within the unstirred layer; the measured difference in ion concentration between the two positions is converted into a corresponding ion flux across the tissue using the Fick equation. Hardware and software used for SIET have been described previously (Naikkhwah and O'Donnell, 2012). K + -selective microelectrodes were backfilled with 150 mmol l…”
Section: Measurement Of Kmentioning
confidence: 99%
“…Positioning was followed by a 4.0 s wait period, during which no measurements were made, to allow the re-establishment of ion gradients at the tissue surface following the localized disturbance of the microelectrode movement. A wait time of 3 s is sufficient to allow the gradients to fully reestablish (Naikkhwah and O'Donnell, 2012). The voltage at the microelectrode tip was then recorded during a sample period of 0.5 s following the wait period.…”
Section: Measurement Of Kmentioning
confidence: 99%
“…Although fluid secretion at the Malpighian tubules is primarily energized by the proton-motive V-ATPase coupled to a H + /K + exchanger, Na + /K + -ATPase in the basolateral membrane of Malpighian tubule principal cells is important in modulating rates of Na + and water secretion (Linton and O'Donnell, 1999;Beyenbach et al, 2010 (Linton and O'Donnell, 1999). High Na + /K + -ATPase activity in the basal membrane of the hindgut is responsible for transporting Na + back into the haemolymph of the mosquito Aedes aegypti (Diptera: Culicidae) (Patrick et al, 2006), and net Na + is transported into the haemolymph in the larval hindgut of D. melanogaster (Naikkhwah and O'Donnell, 2012 + gradients that drive Na + leak and water balance disruption at low temperatures, and thereby improve cold tolerance. This hypothesis is supported by the repeated observation that cold acclimation of insects results in less-polarized muscle Na + equilibrium potentials (Koštál et al, 2004;Koštál et al, 2006;Coello Alvarado, 2012).…”
Section: Introductionmentioning
confidence: 99%